BARCODE SCANNING SYSTEM FOR GOODS TRANSACTIONS USING FIRST IN FIRST OUT (FIFO) METHOD WITH THE LARAVEL FRAMEWORK - Kurnia, Kharis; Azizah, Siti Nur (Edelweiss : Journal Of Innovation In Educational Research, 2025)
Inventory management is an essential aspect of retail operations that requires accuracy and efficiency, particularly in tracking product quantities and expiration dates. Effective inventory management can be achieved by implementing First In First Out (FIFO) method and a barcode scanning system to simplify recording processes and minimize manual errors. This study designs a web-based inventory management system using the Agile method and the Laravel framework as its foundation, featuring barcode scanning, automatic recording of incoming and outgoing goods, FIFO-based inventory management, and notifications for products approaching their expiration dates. Black Box testing results show that the system successfully improves transaction efficiency, inventory management accuracy, and real-time detection of products nearing expiration, thereby reducing the risk of losses at Toko Rindu Mekkah. In terms of educational implications, this research serves as a practical example of integrating inventory management theory with information technology. It can also be used as instructional material to enrich learning in the fields of information technology and information systems, particularly related to application development, the Agile method, and the implementation of the FIFO concept in digital systems.